Tetrabutylammonium Iodide Catalyzed Epoxidation of Naphthoquinone Derivatives with tert-Butyl Hydroperoxide as an Oxidant - Ai, Bai-Ru; Chen, Xu-Ling; Dong, Yu; Tang, Lei; Wang, Ji-Yu (Synthesis, 2017)
An efficient and environmentally benign procedure has been developed for the epoxidation of naphthoquinone derivatives by using tetrabutylammonium iodide as a catalyst and tert-butyl hydroperoxide as an oxidant in the presence of silicon dioxide. This protocol, which provides a facile base-free methodology for the synthesis of some new naphthoquinone-based epoxides, features mild reaction conditions, high yields, remarkably short reaction time, and broad substrate scope
Keywords: naphthoquinone derivates; expoxidation; tetrabutylammonium iodide; tert-butyl hydroperoxide; silicon dioxide